2020
DOI: 10.36740/wlek202003123
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytocin Imbalance in the Development Of Man Infertility

Abstract: The aim: Study of the clinical and pathogenetic role of IL-17, IL-35 and their correlation in the development of infertility in men with chronic ureoprostatitis. Materials and methods: 82 male aged 20 to 40 were examined. The patients were divided into three groups: the first – 10 practically healthy men, in which the levels of IL-17 and IL-35 in semen were taken as normal; second – 33 infertile men with chronic urethroprostatitis; third – 39 fertile men with chronic urethroprostatitis. In addition to conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…In the present study, IL-17A levels on days 3, 7, and 42 after LPS injection increased and could have been correlated with sperm damage. This result is consistent with the study conducted by Babinets et al [ 30 ], who showed that increased Il-17A levels were correlated with male infertility. A study on urinary tract infections (UTIs) caused by uropathogenic E. coli reported that IL-17 was a key mediator of the innate immune response to UTIs [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, IL-17A levels on days 3, 7, and 42 after LPS injection increased and could have been correlated with sperm damage. This result is consistent with the study conducted by Babinets et al [ 30 ], who showed that increased Il-17A levels were correlated with male infertility. A study on urinary tract infections (UTIs) caused by uropathogenic E. coli reported that IL-17 was a key mediator of the innate immune response to UTIs [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, seminal plasma IL-17 level in infertile patients was significantly higher in comparison with healthy controls, which sheds light on its role in the pathogenesis of male infertility. In agreement with our results, Babinets et al [11] found that the concentration of IL-17 increases in infertile men with chronic urethral prostatitis and they concluded that it may be a good biomarker of chronic inflammation of the urogenital tract.…”
Section: Discussionsupporting
confidence: 93%